Distribution and chemical composition of atmospheric aerosols over the Gulf of Thailand during the southwest monsoon - Kayee, Jariya; Sompongchaiyakul, Penjai; Das, Reshmi; Wang, Xianfeng; Chinfak, Narainrit; Arnupapboon, Sukchai; Bureekul, Sujaree (My University, 2026)
Marine aerosols were collected over the Gulf of Thailand (GOT) during the 2018 southwest monsoon on board the M.V. SEAFDEC2 while sailing. Water-soluble inorganic ions (i.e., Na+, NH4+, K+, Mg2+, Ca2+, Cl−, NO3−, and SO42−) and elemental concentrations (i.e., Al, As, Ba, Ca, Cd, Cu, Cr, Fe, Mg, Mn, Na, Ni, Pb, Sr, V, and Zn) were determined to investigate their distribution patterns in order to evaluate the influence of particle sources on the chemical properties of atmospheric aerosols. During the southwest monsoon, the wind predominantly blows over the Indian Ocean to the GOT. Correspondingly, our results indicated that coarse particles are dominated by sea salts. Cl− and Na+ are the major ions, accounting for ∼64.8% (range: 51.2–84.3%) of total ions in the coarse mode particles. The strong correlation between Cl− and Na+ ( r = 0.999) along with the Cl/Na ratio (1.5, range: 0.66–2.00) suggest sea salt origin. Enrichment factor (EF) values indicate that elements are originated from oceanic, crustal, and anthropogenic sources. The oceanic source (Sr, Ca, Mg and Na) explains 95% (range: 81–99%) of total elements in the aerosols. Elements such as Al, Fe, Mn and Ba explain 4.6% of the total elements. These elements associate with the crustal source. Only a minimal amount (0.63%, range: 0.02–4.5%) of the total elements is originated from anthropogenic activities over or nearby the GOT as shown by loading of As, Cd, Cu, Cr, Ni, Pb, V and Zn.
Keywords: PM coarse; PM2.5; The Gulf of Thailand; Trace element; Water-soluble inorganic ion